2020
DOI: 10.1016/j.foodres.2019.108871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ageing time on consumer preference and sensory description of foal meat

Abstract: A consumer test (n=120) was performed in Vitoria-Gasteiz (northern Spain) in order to study the effect of ageing time (0, 7, 14 and 21 days) on the sensory quality of Hispano-Bretón foal meat.Steaks (Longissimus thoracis et lumborum) were wet aged and evaluated in-mouth and visually. In both cases, acceptability was scored using a hedonic scale, and sensory drivers related to ageing were characterised by applying check-all-that-apply method in meat. For both, in-mouth and visual acceptability, meat aged for 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
3
10
0
Order By: Relevance
“…The overall outcomes from the present paper seems to be consistent with results reported in literature nowadays, increasing knowledge on the effect of vacuum aging in horse meat. The increase in volatile compounds during the first nine days of vacuum aging is consistent with the increase of consumer sensorial perception of intensity of flavor/aroma recently reported on vacuum aged horse meat during the same period [ 11 ]. The increase of volatile compounds can be linked to the chemical modifications of fat and protein molecules during storage [ 62 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The overall outcomes from the present paper seems to be consistent with results reported in literature nowadays, increasing knowledge on the effect of vacuum aging in horse meat. The increase in volatile compounds during the first nine days of vacuum aging is consistent with the increase of consumer sensorial perception of intensity of flavor/aroma recently reported on vacuum aged horse meat during the same period [ 11 ]. The increase of volatile compounds can be linked to the chemical modifications of fat and protein molecules during storage [ 62 ].…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies [ 2 , 9 , 10 ] showed that refrigerated vacuum aging for a period of 7–30 days increased the flavor score of cooked meat. This effect has also recently been confirmed in foal meat, although the overall consumer acceptance of vacuum aged horse meat was based more on textural improvement than on flavor/taste increase [ 11 ].…”
Section: Introductionmentioning
confidence: 86%
“…The color changes during ageing period are well illustrated in Figure 3 , where a representative photograph of each ageing time is shown. It is worth commenting that samples aged for 21 d were visually evaluated by 120 consumers and these samples obtained the worst acceptability scores [ 43 ]. After 14 d of ageing, the visually apparent color shift to brownish could be the reason why consumers rejected the meat aged for 21 d, as the cherry-red color that they associate with freshness was not present [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Horses were slaughtered in a commercial abattoir, following the specifications in the European legislation [ 42 ], at 15–17 months of age. More details about the experimental design have been previously described [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The tenderness is closely related to not only the chemical state of myofibrils but also connective tissue, juiciness as well as marbling condition (Aktaş, 2003;Purslow et al, 2016). Recently, wet-aging and sous-vide processing have been recognized as good ways to tenderize meat (Beldarrain et al, 2020). However, these techniques have some limitations regarding microbial control, energy efficiency and commercialization for mass-production.…”
Section: Introductionmentioning
confidence: 99%